Foundations of ultraprecision mechanism design; Vol.2 - Stuart T Smith (Gordon and Breach Science, 1992)
This book provides bridge for those moving from either an ingineering or physics background towards the unique challenges offered by ultraprecision mechanisms. In providing a guide to basic techniques and much vital technical, analytical and practical information